2013
DOI: 10.1021/es304511z
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational Study of Gold Nanoparticles inCaenorhabditis elegans: Transgenerational Effect of Maternal Exposure

Abstract: In this study, the generational transfer and multigenerational effect of gold nanoparticles (AuNPs) on Caenorhabditis elegans were investigated by observing the parental generation (F0) to the fourth offspring generation (F4) using food-exposure approaches. There were no significant changes on survival rate under all generations by AuNP maternal exposure to the F0 generation. However, reproduction rate was clearly affected in the F2 generation but then gradually recovered in the F3 and F4 generations. The abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(76 citation statements)
references
References 33 publications
2
73
1
Order By: Relevance
“…Changes in sensitivity in multigenerational exposed populations changed the expected effect of the continuous exposure concentration from an EC 35 to EC 63 -EC 66 for AgNO 3 and an EC 25 to an EC 55 -EC 73 for Ag-PVP-exposed F2 -F8 generations (electronic supplementary material, table S3). A slight reduction in F10 sensitivity reduced this effect severity for the multigenerational exposure to an EC 19 and EC 13 for AgNO 3 and Ag-PVP, respectively. This resulted from changes in the shape of the response curves with EC 50 levels remaining lower than the P generation.…”
Section: (Ii) Multigenerational Exposurementioning
confidence: 96%
“…Changes in sensitivity in multigenerational exposed populations changed the expected effect of the continuous exposure concentration from an EC 35 to EC 63 -EC 66 for AgNO 3 and an EC 25 to an EC 55 -EC 73 for Ag-PVP-exposed F2 -F8 generations (electronic supplementary material, table S3). A slight reduction in F10 sensitivity reduced this effect severity for the multigenerational exposure to an EC 19 and EC 13 for AgNO 3 and Ag-PVP, respectively. This resulted from changes in the shape of the response curves with EC 50 levels remaining lower than the P generation.…”
Section: (Ii) Multigenerational Exposurementioning
confidence: 96%
“…Importantly, it has been widely employed as a test model in toxicology studies from the whole-animal level down to the single-cell level1019. Moreover, C. elegans has a translucent body that can be exploited to observe the distribution of AgNPs in the organ system.…”
mentioning
confidence: 99%
“…C. elegans has been extensively employed in ENP-related uptake and nanotoxicity studies to investigate the potential deleterious effects of ENP-exposure on organism health and behavior. [6][7][8][9][10][11][12][13][14] For nano-exposure research involving C. elegans, conventional rinsing procedures are typically composed of multiple water or media rinses followed by centrifugation and vacuum filtration of the supernatant. [6-8, 10, 11, 15, 16] When our research group tested and employed a similar rinsing strategy, we found that water rinsing was unsuitable for the efficient removal of non-ingested NPs, even at low, environmentally relevant exposure concentrations (ng mL -1 or part per billion in gold mass fraction).…”
Section: Principles and Scopementioning
confidence: 99%